Altering properties of cerium oxide thin films by Rh doping. (July 2015) - Ševčíková, Klára; Nehasil, Václav; Vorokhta, Mykhailo; Haviar, Stanislav; Matolín, Vladimír; Matolínová, Iva; Mašek, Karel; Píš, Igor; Kobayashi, Keisuke; Kobata, Masaaki; Nagata, Takahiro; Matsushita, Yoshitaka; et al.
Graphical abstract: Highlights: Thin films of ceria doped by rhodium deposited by RF magnetron sputtering. Concentration of rhodium has great impact on properties of Rh–CeO x thin films. Intensive oxygen migration in films with low concentration of rhodium. Oxygen migration suppressed in films with high amount of Rh dopants. Abstract: Ceria containing highly dispersed ions of rhodium is a promising material for catalytic applications. The Rh–CeO x thin films with different concentrations of rhodium were deposited by RF magnetron sputtering and were studied by soft and hard X-ray photoelectron spectroscopies, Temperature programmed reaction and X-ray powder diffraction techniques. The sputtered films consist of rhodium–cerium mixed oxide where cerium exhibits a mixed valency of Ce 4+ and Ce 3+ and rhodium occurs in two oxidation states, Rh 3+ and Rh n + . We show that the concentration of rhodium has a great influence on the chemical composition, structure and reducibility of the Rh–CeO x thin films. The films with low concentrations of rhodium are polycrystalline, while the films with higher amount of Rh dopants are amorphous. The morphology of the films strongly influences the mobility of oxygen in the material. Therefore, varying the concentration of rhodium in Rh–CeO x thin films leads to preparing materials with different properties.